2022
DOI: 10.4236/epe.2022.147015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Solar Power Production in Dry and Rainy Seasons Using Some Selected Meteorological Parameters

Abstract: In this paper, we deployed the multiple linear regression method in developing a solar power output model for solar energy production, where the meteorological parameters are the independent variables. We fitted the model and found that the meteorological variables considered accounted for 94.88% and 99.61% of the power output in both dry and rainy seasons. We observed from the work that the solar panel performs well in all seasons but slightly better in the rainy seasons. This could be attributed to the washi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…From the Analysis of Variance presented in Table 3, we observed that all the parameters such as; Irradiation (X 1 ), Temperature (X 2 ), Wind speed (X 3 ) and Humidity (X 4 ) were significant in solar power output in this quarter, this also correspond to the work of [13]. In this case, we accept the alternative hypothesis (H 1 :) and conclude that these parameters (Irradiation, Temperature, Wind speed and Humidity) contributed significantly to the solar power output.…”
Section: Interpretation Of Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…From the Analysis of Variance presented in Table 3, we observed that all the parameters such as; Irradiation (X 1 ), Temperature (X 2 ), Wind speed (X 3 ) and Humidity (X 4 ) were significant in solar power output in this quarter, this also correspond to the work of [13]. In this case, we accept the alternative hypothesis (H 1 :) and conclude that these parameters (Irradiation, Temperature, Wind speed and Humidity) contributed significantly to the solar power output.…”
Section: Interpretation Of Resultsmentioning
confidence: 71%
“…From the analysis in Table 3, we observe that the fit was very much adequate and a little better than the corresponding fit in work of [13]. This is attributed to precision due to the developed data logger system.…”
Section: Interpretation Of Resultsmentioning
confidence: 75%
See 3 more Smart Citations